2009
DOI: 10.1177/1744987108093962
|View full text |Cite
|
Sign up to set email alerts
|

An overview of mixed methods research

Abstract: Mixed methods research is viewed as the third methodological movement and as an approach it has much to offer health and social science research. Its emergence was in response to the limitations of the sole use of quantitative or qualitative methods and is now considered by many a legitimate alternative to these two traditions. Purists’ view of the dichotomy between positivist and non-positivist philosophies is prevalent; however, mixed methods afford researchers an opportunity to overcome this ‘false dichotom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
216
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 340 publications
(266 citation statements)
references
References 27 publications
1
216
0
6
Order By: Relevance
“…A review of 75 MMR studies in healthcare in the UK found that researchers often ignored their mixed methods design and described only the separate components [32]. Considerable experience and expertise -both in qualitative and quantitative research traditions -would seem to be needed to achieve good integration and good study outcomes [52]. In our case, the project leader, originally purely schooled in qualitative methods, learned to handle quantitative methods as well.…”
Section: Relevance and Application Of Mmr In Health Communication Resmentioning
confidence: 91%
“…A review of 75 MMR studies in healthcare in the UK found that researchers often ignored their mixed methods design and described only the separate components [32]. Considerable experience and expertise -both in qualitative and quantitative research traditions -would seem to be needed to achieve good integration and good study outcomes [52]. In our case, the project leader, originally purely schooled in qualitative methods, learned to handle quantitative methods as well.…”
Section: Relevance and Application Of Mmr In Health Communication Resmentioning
confidence: 91%
“…That led to the emergence of terms such as multi-method research, nested analysis, multiple stranding, mixing, blending, combining and integrating in dealing with both research perspectives. We deliberately prefer to use the term mixed methods research (MMR) as it has gained currency in the extant literature (Doyle, Brady & Byrne, 2009) and it captures nicely the essence of combining research methodologies better than the other terms. MMR is an: umbrella term applying to almost any situation where more than one methodological approach is used in combination with another, usually, but not essentially, involving a combination of at least some elements drawn from each of qualitative and quantitative approaches to research (Bazeley, 2008:133).…”
Section: Contextualising Mixed Methods Researchmentioning
confidence: 99%
“…This mixed methods approach was adopted in order to provide a deeper and richer understanding (Agnew and Flin, 2013) of large-scale improvement collaborative. This approach of using a mixed-methods model is also acknowledged by others (Doyle et al, 2009;O'Cathain et al, 2010); and is now becoming the dominant paradigm in healthcare research. The type of topology of the mixed methods design we used was a qualitative + quantitative, where the two methods -qualitative (QUAL) and quantitative (quan) were undertaken concurrently, but the dominant status was the qualitative study (Johnson and Onwuegbuzie, 2004;Creswell and Plano Clark, 2007).…”
Section: Methodsologymentioning
confidence: 92%